2018
DOI: 10.1038/s41598-018-27748-9
|View full text |Cite
|
Sign up to set email alerts
|

A Markovian Approach towards Bacterial Size Control and Homeostasis in Anomalous Growth Processes

Abstract: Regardless of the progress achieved during recent years, the mechanisms coupling growth and division to attain cell size homeostasis in bacterial populations are still not well understood. In particular, there is a gap of knowledge about the mechanisms controlling anomalous growth events that are ubiquitous even in wild-type phenotypes. Thus, when cells exceed the doubling size the divisome dynamics sets a characteristic length scale that suggests a sizer property. Yet, it has been recently shown that the size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Finally, the plasticity + eco‐evo model assumes that both supply–demand (plastic) and eco‐evo (rapid evolution) contributions can simultaneously influence the rate of change of M , resulting in the following model for body size dynamics:normaldMnormaldtgoodbreak=eKNgoodbreak−cMδgoodbreak+σ2h2F)(MM.This model does not account for possible interplay between plastic and evolutionary change, such as plasticity facilitating evolution, plasticity impeding evolution, or evolving plasticity, all of which can occur and have been reviewed elsewhere (Diamond & Martin, 2016). None of our models account for shifts in age or size structure because we were specifically interested in mathematically tracking changes in mean body size, not changes in the entire trait distribution, which require model formulations that are not amenable to ODE fitting (Chen et al, 2018; Nieto‐Acuña et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the plasticity + eco‐evo model assumes that both supply–demand (plastic) and eco‐evo (rapid evolution) contributions can simultaneously influence the rate of change of M , resulting in the following model for body size dynamics:normaldMnormaldtgoodbreak=eKNgoodbreak−cMδgoodbreak+σ2h2F)(MM.This model does not account for possible interplay between plastic and evolutionary change, such as plasticity facilitating evolution, plasticity impeding evolution, or evolving plasticity, all of which can occur and have been reviewed elsewhere (Diamond & Martin, 2016). None of our models account for shifts in age or size structure because we were specifically interested in mathematically tracking changes in mean body size, not changes in the entire trait distribution, which require model formulations that are not amenable to ODE fitting (Chen et al, 2018; Nieto‐Acuña et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…None of our models accounts for shifts in age or size structure because here we were are specifically interested in mathematically tracking changes in mean body size, not changes in the entire trait distribution, which also requires model formulations that are not amenable to ODE fitting (Chen, Baños & Buceta 2018; Nieto-Acuña et al . 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Filamentation can also be triggered by exposure to antibiotics (Bos et al, 2015; Chatterjee & Raychaudhuri, 1971; Goormaghtigh & Van Melderen, 2019; Hunt & Pittillo, 1968; Klein & Luginbuhl, 1977; Raghunathan et al, 2020; Ryan & Monsey, 1981; Spratt, 1975) or genetic mutations that specifically inhibit fundamental cell cycle processes, such as DNA replication, cell division or DNA recombination (Allen et al, 1972, 1974; Bi & Lutkenhaus, 1991; Breakefield & Landman, 1973; Ishioka et al, 1998; Lloyd et al, 1988; Mulder & Woldringh, 1989; Rudolph, Upton, Harris, et al, 2009; Rudolph, Upton, & Lloyd, 2009; Van De Putte et al, 1964). Part of these studies reported that filamentation is a reversible morphological change as filaments are generally able to resume division upon return to favorable conditions (Adler & Hardigree, 1965; Barrett et al, 2019; Bos et al, 2015; Chen et al, 2018; Dev Kumar et al, 2019; Goormaghtigh & Van Melderen, 2019; Heinrich et al, 2019; Ishioka et al, 1998; Mulder & Woldringh, 1989; Pribis et al, 2019; Raghunathan et al, 2020; Rudolph et al, 2007; Rudolph, Upton, Harris, et al, 2009; Söderström et al, 2022; Wehrens et al, 2018; Woldringh et al, 1991). Filamentation is even part of the normal life cycle of some bacterial organisms, such as Caulobacter crescentus in freshwater (Allison et al, 1992; Heinrich et al, 2019), the cyanobacterium Synechococcus elongatus growing under dim light (Liao & Rust, 2018) or Legionella pneumophila within biofilms (Piao et al, 2006).…”
Section: Introductionmentioning
confidence: 99%